Clinical Tools to diagnose Eustachian tube Dysfunction in patients with a normal tympanic membrane exam and a type A tympanogram - Roya Azadarmaki (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Objective: Obstructive Eustachian tube dysfunction, a form of Eustachian tube dilatory dysfunction, can be a challenge to diagnose in individuals with classic Eustachian tube dysfunction symptoms but a normal tympanic membrane exam and tympanogram. The purpose of this article is to outline techniques that can be used by the otolaryngologist to evaluate patient's under these circumstances. Methods: Eustachian tube dysfunction was assessed combining fi ndings from dynamic evaluation of the tympanic membrane with videoendoscopic evaluation of the Eustachian tube. The "Azadarmaki technique" of assessing the tympanic membrane for eustachian tube dysfunction involves evaluating the tympanic membrane live with a microscope or endoscope while the patient is performing the Valsalva maneuver followed by an immediate swallow.